Successful Treatment by Surgery and Lenvatinib of a Patient with Adrenal Metastasis of Papillary Thyroid Cancer - Hajime Nakamura; Kohichi Takada; Kazuyuki Murase; Hiroki Sakamoto; Naotaka Hayasaka; Kazuma Ishikawa; Yuki Ikeda; Makoto Yoshida; Satoshi Iyama; Ko Kobayashi; Tetsuya Shindo; Shintaro Sugita; et al. (Case Reports in Oncological Medicine)
Papillary thyroid cancer (PTC) is considered an indolent cancer, but some PTC patients do present with distant metastases and treatment strategies for such patients are not well established. Recently, lenvatinib, an inhibitor of multiple tyrosine kinases, has been introduced to treat patients with advanced PTC but carries a risk of serious adverse events such as hemorrhage. Here, we report a PTC patient with a left adrenal metastasis and lenvatinib-induced hemorrhage who underwent successful surgical resection and was subsequently treated with a lower dose of lenvatinib. The patient has now been in a stable state with no adverse events for nearly two years. This case highlights the importance of surgical resection of metastatic PTC and subsequent lenvatinib therapy, even when the tumor is at an advanced stage.